Management information systems : - Post, Gerald V. (McGraw-Hill/Irwin, 2003)
This book focuses on how managers can apply knowledge of IT tools to solve management problems and find new opportunities to improve their organizations. This revised edition addresses these challenges and continues to illustrate how information technology supports managers in their operational and decision-making tasks performed each day.